The distribution of a distance from inside point of oval to its contour - Gečiauskas, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Гячяускас. Распределение расстояния от внутренней точки овала до его контура E. Gečiauskas. Atstumo nuo ovalo taško iki jo kontūro pasiskirstymas